1993
DOI: 10.1080/07435809309035409
|View full text |Cite
|
Sign up to set email alerts
|

CD5+B Lymphocytes and CD4+CD45RA+T Cells in Graves' Disease

Abstract: Fifteen patients affected by new-onset Graves' disease with ophthalmopathy have been examined for lymphocyte subset phenotypes by two-colour cytometric analysis. CD5+ B cells were significantly increased in comparison to the normal population (43.2 +/- 20.6% versus 19.5 +/- 6.9%; p < 0.0009); total T cells showed a normal amount (70.4 +/- 9.6%), but the levels of THLADR+ cells were significantly increased in comparison to the control group (13.7 +/- 10.5% versus 4.7 +/- 3.2%; p < 0.007). The characterization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
8
0

Year Published

1995
1995
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…That finding is confirmed by our data, although some deviating observations have been made by others (34), who even observed an increased proportion of CD8+ cells (35). In addition, a greater number of B cells among lymphocytes was seen in patients with GD than in healthy subjects.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…That finding is confirmed by our data, although some deviating observations have been made by others (34), who even observed an increased proportion of CD8+ cells (35). In addition, a greater number of B cells among lymphocytes was seen in patients with GD than in healthy subjects.…”
Section: Discussionsupporting
confidence: 92%
“…Changes in the proportion of CD4+ and CD8+ T cells have been observed in different disease settings, including AITD (20,(32)(33)(34)(35), which in the majority of reports displayed a reduction in circulating CD8 cells in GD and only in part also in AH (32). That finding is confirmed by our data, although some deviating observations have been made by others (34), who even observed an increased proportion of CD8+ cells (35).…”
Section: Discussionsupporting
confidence: 89%
“…9,10 Our case demonstrated the polyclonal activation of B cells, which lead to the production of several types of organ-specific autoantibodies (anti-TPO antibody, anti TSH-Rab) and a non-organspecific autoantibody (anti-MPO antibody) at one time. Harper et al concluded that the altered immune environment associated with autoimmune thyroid disease is not sufficient to develop ANCA but treatment with PTU is important in promoting ANCA development.…”
Section: Discussionmentioning
confidence: 78%
“…The antibody titer was highest in patients with Graves' disease and decreased with methimazole treatment. Likewise, Marongiu found an increased incidence of APLA positivity in Graves' disease patients compared to healthy controls [6]. In these patients the antibody was of the IgG subtype.…”
Section: Discussionmentioning
confidence: 83%
“…However, other autoantibodies, including APLA, that are not thyroid specific have been detected in these patients [4]. The clinical significance of these antibodies is uncertain: some have reported that while patients with ATD may have circulating APLA they do not manifest any of the clinical abnormalities associated with the APLA syndrome while others have claimed that the presence of APLA may have clinical significance [5][6][7]. We recently encountered four patients with ATD in whom thromboembolic phenomena occurred.…”
mentioning
confidence: 99%